Effects of planting alfalfa on soil quality in desert steppe of Ningxia - Chen Lin; Yang Xinguo; Song Naiping; Li Xuebin; Zhai Deping (浙江大学学报. 农业与生命科学版, 2014)
Soil quality plays a crucial role in sustaining agricultural systems productivity, and it is important in sustaining ecosystem. What about the soil quality in different planting years of alfalfa (Medicago sativa) in the steppe desert of Ningxia in China?That is not yet completely understood.The objective of this study was to investigate the soil physical and chemical properties of different soil particle diameters (>0.5 mm,0.106-0.25 mm and <0.106 mm) after planting alfalfa for 0-12 years.By using the method of replacing time with space, an analysis was made on the dynamic changes of top soil (0-20 cm and 20-40 cm) nutrients and soil particle. The results showed that there was no significant difference between the different soil particle diameters in the same period of the pH, electrical conductivity (EC), soil organic matter (SOM), CaCO3, total nitrogen (TN), available nitrogen (AN), total phosphorus (TP) and available phosphorus (AP)(P>0.05), but the soil active organic carbon (SAOC) contents of the soil particle with diameters of >0.5 mm and < 0.106 mm were significantly higher than that of soil particle with diameters of 0.106-0.25 mm (P<0.05). With the increasing of planting years, the pH values decreased, and after planting alfalfa, it was greater affected in 20-40 cm soil layer than 0-20 cm soil layer. The EC values were fluctuated in different planting years, but there were not significant (P>0.05), and the EC values of 0-20 cm soil layer were significantly higher than that of 20-40 cm soil layer in most planting years. The SOM contents in each planting year were higher than the grass, but there was no significant difference (P>0.05), and the SOM contents of soil particle with diameters of >0.5 mm and <0.106 mm in 0-20 cm soil layer were increased firstly (1 year) and then decreased (4-12 years) with the increase of planting years, while the SAOC contents of 20-40 cm soil layer remained unchanged. The SAOC contents of soil particle with diameters of >0.5 mm and <0.106 mm in 0-40 cm soil layer in each planting year were significantly higher than that of soil particle with diameters of 0.106-0.25 mm (P<0.05), but there was no significant difference in each planting year (P>0.05). The TN and AN contents in 0-40 cm soil layer fluctuated a lot and showed no influence on TN content. The TP contents of 0-40 cm soil layer and the AP contents of 0-20 cm soil layer showed the increasing trend (0-12 years), and the AP contents of 20-40 cm soil layer showed the “M” type fluctuations. The TP contents of 0-20 cm soil layer were significantly lower than those of the 20-40 cm soil layer in 1-12 years (P<0.05). The C/N values of 0-20 cm soil layer were higher than those of the 20-40 cm soil layer in the same planting years, and in 12 years, the C/N value was significantly lower than other years (P<0.05). The CaCO3 contents of 0-40 cm soil layer showed an increasing trend with the increasing of planting years, and the CaCO3 contents of 20-40 cm soil layer were significantly higher than those of 0-20 cm soil layer (P<0.05).In conclusion, with the increasing of planting years, there was significant difference only between the soil particle diameter and the SAOC content (P<0.05), and the soil quality showed temporal variability.